Home INR monitoring for paediatric congenital heart disease patients – is it safe?. Issue 5 (22nd April 2012) - Moore, E; Gage, S; Forsey, J; Harrington, C; Tometzki, A
Abstract : Objective: To assess the safety and efficacy of home international normalised ratio (INR) monitoring (near point testing) using the Coaguchek machine with support and advice from the paediatric cardiac team and to assess variance from the National Patient Safety Agency (NPSA) Alert 18 ('Actions that can make anticoagulant therapy safer') safety indicators. Method: An audit form was designed and the audit was conducted by a medical student. The study period was between 1st July 2009 and 31st May 2010. A retrospective study, that included all the paediatric congenital heart disease patients, maintained on warfarin, via near point testing in the community, who were dosed by the paediatric cardiac team. Patients were identified from the cardiac database (Heartsuite) and the anticoagulation records. Standards were taken from the NPSA Alert 18 safety indicators and included; the number of INRs measured, percentage within range, numbers greater than INR of 5 and 8 and INRs less than one unit below target range. The audit also reviewed major bleeding episodes and annual review at an anticoagulation clinic. Results: 50 patients were identified. The median age was 10 years (range: 8 months to 18 years). The indications for warfarin were varied and included fontan circulations, mechanical valves, thromboembolic events, cardiomyopathy and other surgical indications. The majority of patients had INRs at the recommended time intervals. Two thirds of INRs were within target ranges. There were only three children with an INR greater than eight but there were no episodes of major bleeding. There were no serious adverse events; all patients had a target INR documented in their medical case notes. Conclusion: Anticoagulation with warfarin in the paediatric population is challenging due to intercurrent illness, childhood development and concurrent medication contributing to variations in bioavailability and hence changes in INR. The NPSA recommendations were driven by the need for safe anticoagulation in the adult population on long-term anticoagulation monitored in community. They are not flexible enough to accommodate the very different prospect of safely anticoagulating a child with complex congenital heart disease. The results demonstrate that home INR monitoring with proper education and liaison provides a safe and effective treatment option for cardiac children requiring warfarin. This is especially important for our geographical area in the South-West and perhaps is a model that could be used in other regions.